Unraveling Islamic Social Finance Accounting Research: Bibliometric Analysis and Systematic Literature Review (SLR) - Lisnaeni, Lisnaeni; Handoko, Luqman Hakim; Lubis, Ahmad Tarmizi (Jurnal Akuntansi dan Keuangan Islam, 2023)
This study aims to unravel Islamic social finance accounting research. The research method uses bibliometrics and SLR. The data type used is secondary data from 98 articles indexed by Scopus. Data is visualized using VOSViewer. The results show that the research distribution began in 1995. The peak of publication will be in 2021, with 15 publications. The most popular writer is Masruki R. with his 5 articles. The Journal of Islamic Accounting and Business Research is the most productive and popular journal, with 9 published articles and 149 citations. Malaysia is the most productive and most popular country, with 49 articles and 406 citations. The most popular author is Zaid O. A., with 77 citations. The most popular article, which gets 49 citations, written by Yalya H.E., discusses changes in the accounting and accountability of Sultan Sulaiman's waqf in the Ottoman Empire. USIM is the most productive university, with overshadowing 24 writers. While, IIUM is the most popular institution, with 179 citations. The following research directions are based on co-occurrence analysis through networks, density, and overlay visualization, as well as SLR analysis of zakat, infaq /alms accounting focusing on transparency, Sharia compliance, disclosure of socio-economic impact, and Enterprise Resource Planning (ERP). Meanwhile, the theme of waqf accounting focuses on disclosure, transparency, and optimization of Cash Waqf Linked Sukuk (CWLS), as well as opportunities and challenges in waqf reporting practices.Penelitian ini bertujuan untuk mengungkap penelitian akuntansi keuangan sosial Islam. Metode penelitian menggunakan bibliometrik dan SLR. Jenis data yang digunakan adalah data sekunder dari 98 artikel yang terindeks Scopus. Data divisualisasikan menggunakan VOSViewer. Hasilnya menunjukkan sebaran penelitian dimulai pada tahun 1995. Puncak publikasi pada tahun 2021 sebanyak 15 publikasi. Penulis terpopuler adalah Masruki R. dengan 5 artikelnya. Journal of Islamic Accounting and Business Research merupakan jurnal paling produktif dan populer, dengan 9 artikel terbit dan 149 sitasi. Malaysia adalah negara paling produktif dan terpopuler, dengan 49 artikel dan 406 kutipan. Penulis terpopuler adalah Zaid O.A., dengan 77 kutipan. Artikel terpopuler yang mendapat 49 sitasi ini ditulis oleh Yalya H.E. membahas tentang perubahan akuntansi dan pertanggungjawaban wakaf Sultan Sulaiman di masa Kesultanan Utsmaniyah. USIM merupakan universitas paling produktif dengan menaungi 24 penulis. Sedangkan IIUM merupakan institusi terpopuler dengan 179 sitasi. Arahan penelitian berikut ini didasarkan pada analisis co-occurrence melalui visualisasi jaringan, kepadatan, dan overlay, serta analisis SLR zakat, akuntansi infaq/sedekah yang berfokus pada transparansi, kepatuhan syariah, pengungkapan dampak sosial ekonomi, dan Perencanaan Sumber Daya Perusahaan. (ERP). Sedangkan tema akuntansi wakaf berfokus pada keterbukaan, transparansi, dan optimalisasi Cash Waqf Linked Sukuk (CWLS), serta peluang dan tantangan dalam praktik pelaporan wakaf.